Analisis IOS dan struktur modal terhadap nilai perusahaan sektor consumer goods - Fransiscus Marcel Chris Danyarto; Yani Monalisa (Vikara: Student Academic Journal of Business and Management, 2026)
This study aims to analyze the effect of the investment opportunity set (IOS) and capital structure (CS) on firm value (FV). The data were obtained from the annual financial reports of consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. This research employs a quantitative approach using secondary data. Out of a total of 61 consumer goods companies, 40 firms were selected as the sample and analyzed using multiple linear regression. The findings indicate that the variables market-to-book value of assets and debt-to-equity ratio have a partial effect on FV, whereas capital expenditure to book value of assets does not have a partial effect on FV. Simultaneous testing reveals that IOS and CS jointly exert a significant influence on FV, underscoring the importance of these factors in corporate financial performance.